Profil Regulasi Emosi dan Implikasinya bagi Bimbingan dan Konseling - Asri Maesaroh; Evi Afiati; Rahmawati Rahmawati (Ma'soem University, 2022)
AThe purpose of this study is to get an overview of emotion regulation, then design a guidance and counseling program to improve emotion regulation in class VIII students of SMP Negeri 10 Serang City for the 2020/2021 academic year. The approach used is a quantitative approach with a descriptive method. The population is class VIII students as many as 343 people, sampling using a simple random sample technique so that the research subject is obtained as many as 185 respondents. The research technique uses a questionnaire or questionnaire consisting of 38 statement items with a reliability value of 0.80 (very high). The instrument scale used is derived from four aspects of emotion regulation, namely the ability to regulate emotion strategies, the ability not to be affected by negative emotions, the ability to control emotions, and the ability to receive emotional responses. The results obtained are that most of the students are in the medium category, namely 144 students with a percentage of 77.83%. The data obtained were then analyzed using descriptive quantitative analysis techniques. After knowing the level of emotion regulation, the design of the guidance and counseling program is made according to the needs based on the results of the research.